Chemical analysis of substitute drugs of abuse – “legal highs” from Lubuskie province, Poland - Mruczyk, Kinga; Durkalec-Michalski, Krzysztof; Jeszka, Jan; Lipińska, Joanna; Stefański, Zbigniew (Journal of Medical Science, 2014)
Introduction. Interest in substitute drugs of abuse, commonly called “dopalacze” [literally “after-burns”] that is “legal highs”, in Poland and abuse of such products, which could pose a significant life hazard, led to legislative action taken by the government. The decision by the Chief Sanitary Inspectorate made shops commonly called “smart shops” close down, while confiscated products were subjected to chemical analyses by national research institutes.Aim. Determination of the chemical composition and possible presence of active substances contained in tested samples of substitute drugs of abuse.Material and methods. The research material consisted of 171 samples taken for analysis at the end of 2010 from retailers in Lubuskie province. Samples of “legal highs” were tested in a specialized laboratory of the Institute of Rural Medicine, Lublin, by means of liquid chromatography with mass spectrometry (HPLC-MS).Results. Laboratory analyses of “legal high” samples showed the presence of different psychoactive substances in 136 samples, representing 80% of the tested products. The compounds included psychoactive substances – MDPV (17%), 4-EMC (10%), AM-694 (10%), JWH-203 (7%), TFMPP (6%), as well as narcotics, such as mephedrone (5% samples), Piper methysticum (5%), JWH-250 (4%), JWH-200 (5%) and Salvia divinorum (2%). Chemical analyses showed that only 35 samples contained no substances that would affect the physiological and psychological condition of the human body.Conclusions. Analyses of the chemical composition of “legal highs” showed that they contained a large group of different substances or their mixtures exhibiting psychoactive and narcotic activity that may pose a significant health and life hazard.